59.5k views
4 votes
Solve the following system of equations using an augmented matrix and Gauss-Jordan Elimination. Be sure to show your work and explain what you are doing. Then, interpret your answer in terms of the original system.

Solve the following system of equations using an augmented matrix and Gauss-Jordan-example-1

1 Answer

4 votes

Okay, here we have this:

Considering the provided equation, we are going to solve the system using an augmented matrix and Gauss-Jordan Elimination. So we obtain the following:


\begin{gathered} \begin{bmatrix}3x+2y-4z=4 \\ x-3y-10z=8 \\ -5x-4y+12z=-2\end{bmatrix} \\ \begin{bmatrix}(4-2y+4z)/(3)-3y-10z=8 \\ -5\cdot(4-2y+4z)/(3)-4y+12z=-2\end{bmatrix} \\ \begin{bmatrix}(-11y-26z+4)/(3)=8 \\ (-2y+16z-20)/(3)=-2\end{bmatrix} \\ \begin{bmatrix}(-2\left(-(26z+20)/(11)\right)+16z-20)/(3)=-2\end{bmatrix} \\ \begin{bmatrix}(4\left(19z-15\right))/(11)=-2\end{bmatrix} \\ y=-(26\cdot(1)/(2)+20)/(11) \\ y=-3 \\ x=(4-2\left(-3\right)+4\cdot(1)/(2))/(3) \\ x=4 \\ \end{gathered}

Finally we obtain that the solution to the system is:


x=4,\: z=(1)/(2),\: y=-3

User Plamen Nikolov
by
5.4k points